Medical students’ behavioral intention to adopt electronic health record system - Md. Nazmus, Sakib; Mohamed Razi, Mohamed Jalaldeen (2017)
Electronic Health Record (EHR) is a computerized system that collect, store and display the data of patients. The use of EHR systems is increasing globally and numbers of countries, both developed and developing, have invested in EHR with a hope of developing their health sector. Accordingly, Bangladesh, a developing country, has shown its keen interest on digitization of health sector. However, very limited information is available on medical professionals’ perception towards EHR. Therefore, the current study aims to understand the level of behavioral intention towards EHR among medical students of two selected medical colleges in Bangladesh. The study also investigates the predictors of behavioral intention. The study adapts Unified Theory of Acceptance and Use of Technology (UTAUT) to match the context. Self-administered questionnaire survey method was used to collect data among 238 medical students from the two selected medical colleges using convenient sampling. Upon completion of data collection, the data were analyzed using SPSS 16 (Descriptive analysis) and AMOS 16 (Measurement model and Structural model). The results showed that the respondents are moderately intended to adopt EHR while Performance Expectancy (PE) and Effort Expectancy (EE) are strong determinants of intention to adopt EHR. EE’s positive effects on EE and Social Influence (SI) also established. The findings of this study might help the policy makers in Bangladesh in their strategy formulation, especially in the health sector, in the future.